1989
DOI: 10.1084/jem.169.6.2133
|View full text |Cite
|
Sign up to set email alerts
|

Interleukins and IgA synthesis. Human and murine interleukin 6 induce high rate IgA secretion in IgA-committed B cells.

Abstract: Freshly isolated murine PP B cells were cultured with 10 different cytokines, including IL-1 alpha, IL-2, IL-4, IL-5, IL-6, IL-7, IFN-gamma, TNF-alpha, and TGF-beta, to investigate a possible role for these cytokines in induction of Ig synthesis. Of interest was the finding that only IL-5 and both mouse recombinant (mr) and human recombinant (hr) IL-6 enhanced IgA synthesis. The effect was greater with either mrIL-6 or hrIL-6 than with mrIL-5. IL-6 induced cycling mIgA+ PP B cells to secrete high levels of IgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
168
3
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(187 citation statements)
references
References 59 publications
14
168
3
1
Order By: Relevance
“…Although the precise cytokine signals required for the induction of secretory-IgA are not completely understood, it has been shown that mucosal IgA responses are supported by both Th1-and Th2-type cell-derived cytokines (26,42,43). Clearly, both serum and mucosal Ag-specific Ab responses were enhanced as a result of the effects of RANTES.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise cytokine signals required for the induction of secretory-IgA are not completely understood, it has been shown that mucosal IgA responses are supported by both Th1-and Th2-type cell-derived cytokines (26,42,43). Clearly, both serum and mucosal Ag-specific Ab responses were enhanced as a result of the effects of RANTES.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated cells were Ͼ93% B220 ϩ as determined by FACS. The cells were centrifuged, counted after staining with trypan blue, plated at 5 ϫ 10 6 cells per well (24-well plate), and cultured with 8 g/mL of LPS from E. coli 0111:B4 in B cell medium (RPMI 1640, 10% FCS, 1% penicillin/streptomycin, and 50 M 2-mercaptoethanol) for 16 h as previously reported (31)(32)(33). Treated cells were diluted to 1 ϫ 10 5 cells per well (96-well plate) into medium containing the indicated cytokines (TGF-␤1, IL-5, and IL-2) with or without oxysterols (250 nM) in triplicate.…”
Section: B Cell Experimentsmentioning
confidence: 99%
“…In the intestinal mucosa during sepsis, endotoxemia, and severe injury, the enterocyte increases its production of IL-6 (12). Although in the short term the beneficial effects of IL-6 includes enterocyte acute phase protein induction, mucosal protein synthesis and IgA production in Peyers patch B cells elevated IL-6 may impair mucosal integrity (13,14).…”
mentioning
confidence: 99%